Investigations On Salivary Gland And Ectopic Pairing In Drosophila Immigrans - KAMLA UPADHYAY; B.K.SINGH (International Journal of Pharma and Bio Sciences, 2012)
Drosophila immigrans were examined using the air-dried technique and a salivary gland map of Drosophila immigrans was constructed. The polytene chromosomes exhibit various ectopic associations and it is assumed that these sites of ectopic paring are the active sites of various protein targets; several identifiable landmarks on salivary chromosomes arms were recognized along with the nucleolar chromatin threads (NCTs), Nucleolar Organizer Regions (NORs) of Drosophila immigrans.